2016
DOI: 10.1007/s13277-015-4746-7
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord mesenchymal stem cells delivering sTRAIL home to lung cancer mediated by MCP-1/CCR2 axis and exhibit antitumor effects

Abstract: Mesenchymal stem cells (MSCs) are believed to be a potential vehicle delivering antitumor agents for their tumor-homing capacity, while the underlying mechanism is yet to be explored. The apoptotic ligand TNF-related apoptosis-inducing ligand (TRAIL) has been suggested as a promising candidate for cancer gene therapy owing to its advantage of selectively inducing apoptosis in cancer cells while sparing normal cells. An isoleucine zipper (ISZ) added to the N-terminal of secretable soluble TRAIL (sTRAIL) can gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The analysis showed for all MSC groups only slightly elevated serum ALT levels compared to PBS group (<50 U/l), but low compared to the Fas ligand treatment known to cause acute liver toxicity (Figure 5D). This result revealed that the applied treatment protocol (three MSC administrations with and without BZB) did not induce discernable acute hepatotoxic effects in vivo , in accordance with a recent study from Yan and colleagues (21). Additionally, all the other standard parameters, such as body weight, remained in the normal range for the entire period of treatment (data not shown).…”
Section: Resultssupporting
confidence: 91%
“…The analysis showed for all MSC groups only slightly elevated serum ALT levels compared to PBS group (<50 U/l), but low compared to the Fas ligand treatment known to cause acute liver toxicity (Figure 5D). This result revealed that the applied treatment protocol (three MSC administrations with and without BZB) did not induce discernable acute hepatotoxic effects in vivo , in accordance with a recent study from Yan and colleagues (21). Additionally, all the other standard parameters, such as body weight, remained in the normal range for the entire period of treatment (data not shown).…”
Section: Resultssupporting
confidence: 91%
“…It is well known that MSCs are inherently tumor-homing cells that, few hours after systemic injection, migrate in the lungs [ 14 , 15 ]. Many receptors, extracellular matrix proteins, and soluble tumor-derived factors have been reported to effect tumor tropism of intravenously injected MSCs [ 15 , 16 ]. Most recently, it was shown that macrophage migration inhibitory factor (MIF)/CXCR4 and monocyte chemoattractant protein-1 (MCP-1)/CCR2 pathways are responsible for migration of MSCs in the tumor microenvironment of the lungs [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many receptors, extracellular matrix proteins, and soluble tumor-derived factors have been reported to effect tumor tropism of intravenously injected MSCs [ 15 , 16 ]. Most recently, it was shown that macrophage migration inhibitory factor (MIF)/CXCR4 and monocyte chemoattractant protein-1 (MCP-1)/CCR2 pathways are responsible for migration of MSCs in the tumor microenvironment of the lungs [ 15 , 16 ]. MIF secreted from tumor cells attracts MSCs to the lungs in CXCR4-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, it is evident that at least a hexavalent organization of TRAIL molecules bypass the pharmacokinetic problems, however not the trimeric form (18). In contrast, in order to manage the insufficient pharmacokinetic properties, several studies have examined the practice of in situ production of a standard soluble TRAIL molecule by different adult stem cells (19)(20)(21). Furthermore, two studies have reported the antitumor activity of human genetically modified MSCs expressing antibodies in a diabody format (22,23).…”
Section: Introductionmentioning
confidence: 99%